Bank efficiency during the current economic crisis: An international comparison - Adrian Babin (Charles University in Prague, Institute of Economic Studies (IES), 2013)
This paper uses a Latent Class Stochastic Frontier Approach to factor out the heterogeneity in the data and to provide evidence on the existence of different bank technologies in international banking with different response schedules to external shocks and diverse constraints. We use an unbalanced panel of 756 banks from 77 countries during 2005-2010 for this purpose. Using bank level structural variables we determine four different profit and cost banking technologies in the data. Further analysis indicates heterogeneity not only among the level of profit and cost efficiency, but also regarding the response of banks to the crisis. Interestingly, we find that banks from the same class but from different regions had a different efficiency evolution over the period. Moreover, we document the existence of banks that are more predisposed to be efficient in certain regions than in others. Finally, we document that banks have several potential options for rebalancing the balance sheet for improving the efficiency, albeit some of these strategies have opposite effects on the profit and cost efficiency.
Keywords: G21; G28; 330; efficiency; heterogeneity; crisis; latent classes